Ser968Thr Mutation within the A3 Domain of Von Willebrand Factor (VWF) in Two Related Patients Leads to a Defective Binding of VWF to Collagen - Ribba, Anne-Sophie; Loisel, Irmine; Lavergne, Jean-Maurice; Juhan-Vague, Irène; Obert, Bernadette; Cherel, Ghislaine; Meyer, Dominique; Girma, Jean-Pierre (Thrombosis and Haemostasis, 2001)
We report the identification of a new mutation of von Willebrand Factor (VWF) gene within exon 30 occurring in two related patients (mother and daughter) with a hemorrhagic syndrome. A T A transvertion at nucleotide 5441 was found changing the serine 968 to threonine of the mature VWF subunit (S1731T of the preproVWF). The Ser968Thr mutation is located within the VWF A3 domain which interacts with type I and III collagens. Both patients were found to be heterozygous for the mutation. The propositus (daughter) exhibited a slightly prolonged bleeding time, levels of VWF:Ag and VWF:RCo at the lower limit of normal, contrasting with normal levels of VIII:C. Her mother exhibited borderline bleeding time and moderately decreased levels of VWF and VIII:C. In both patients multimeric structure of VWF and ristocetin- as well as botrocetin-induced binding of VWF to GPIb were normal; however both patients repeatedly showed decreased binding of VWF to collagen. The Ser968Thr substitution was reproduced by site-directed mutagenesis on the full-length cDNA of VWF. The mutated recombinant VWF (rVWF), T968rVWF, and the hybrid S/T968rVWF were transiently expressed by COS-7 cells. Both rVWF exhibited normal multimeric pattern and normal ristocetin- as well as botrocetin-induced binding to GPIb. T968rVWF showed significantly decreased binding to collagen while the hybrid S/T968rVWF bound to collagen in a similar way to that of the patients’ plasma VWF. Thus, our data demonstrate that the Ser968Thr mutation of the VWF A3 domain is clearly responsible for the abnormal binding of VWF to collagen observed in both patients. The Ser968Thr substitution of the VWF is the first mutation identified in two patients leading to a decreased affinity of VWF for collagen and a normal multimeric structure.
Keywords: Recombinant von Willebrand factor; collagen binding; mutation; COS-7 cells transfection